International Cooperation for Peace in Colombia: The Cases of the United States and the European Union (1998-2016) - Agudelo Taborda, Jairo; Riccardi, Davide (Geopolítica(s). Revista de estudios sobre espacio y poder, 2019)
Since the failed dialogues of the Caguán between FARC-EP and the Colombian Government (1998-2002) until the signature and the referendum of the Havana Agreements (2016), Colombia experienced an intense international support in its search for a negotiated peace. During these years, statistical and documentary analysis have shown that the resources of international cooperation came, mostly, from the two most important partners of Colombia: the United States and the European Union. The first country, privileging a military component; the second actor, based solely on civil assistance. These two different, and sometimes opposed, policies of cooperation for peace reflect distinct interests in both donors (US and EU) and the petitioners (the Colombian State and its civil society). However, the two different cooperation policies converged around the Havana dialogues (2012-2016), and with the signing of the agreements, Colombia took a path towards a new and unprecedented scenario: the “post-conflict”, better known as “post-agreement”. It is precisely this convergence of the two major hegemonic approaches to international cooperation that makes Colombia a sui generis country when it comes to talking about scenarios of conflict and a transition towards post-conflict contexts that could be representative for other geographical circumstances, feeding and fostering the debate between “liberal peace” and “post-liberal peace” for future specific research on this topic.